Genetic analysis of abiotic stress tolerance in crops - Roy, Stuart J; Tucker, Elise J; Tester, Mark (Current opinion in plant biology, 2011)
► Abiotic stresses, such as drought and salinity, have major impacts on crop production. ► Mechanisms by which crops maintain yield under abiotic stress are poorly understood. ► Natural variation in plants useful to elucidate mechanisms of tolerance. ► High-throughput phenotyping required for genetic analysis of tolerance traits. ► Plenty of candidate genes/locus available for crop improvement. Abiotic stress tolerance is complex, but as phenotyping technologies improve, components that contribute to abiotic stress tolerance can be quantified with increasing ease. In parallel with these phenomics advances, genetic approaches with more complex genomes are becoming increasingly tractable as genomic information in non-model crops increases and even whole crop genomes can be re-sequenced. Thus, genetic approaches to elucidating the molecular basis to abiotic stress tolerance in crops are becoming more easily achievable.